A new genus and species of Agalliini from China (Hemiptera, Cicadellidae, Megophthalminae) - Li, Hu; Li, Zi-Zhong (Zootaxa, 2012)
A new monobasic genus and species of the tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) from Guizhou province of China is described and illustrated. Spinoagallia gen. nov. accommodates S. freytagi sp. nov.. The new species can be distinguished mainly by the unique characters of the male genitalia, combining the macrosetae on the outward and spine-like process curved ventrally on the inward pygofer caudodorsal lobe. A key for identification to new genus based on modifying primal key by Viraktamath (2011) is given. A map showing the geographic distribution of the new species is also provided.